Case Report: A Rare Co-Incidence Chronic Appendicitis with Koch’ Abdomen - Saroj, Jitendra Kumar (British Journal of Healthcare and Medical Research, 2022)
Appendicitis is a common disease while abdominal tuberculosis is rare. Diagnosing appendicitis is comparatively easier while for abdominal tuberculosis till date no definitive diagnostic tool is available. All Clinical, hematological and radiological only support the diagnosis but not confirm the diagnosis. In this study both appendicitis and abdominal tuberculosis were present simultaneously which is very rare incidence in medical literature.